Sperm chromatin dispersion by formaldehyde in Wistar rats - Betancourt Martínez, Nadia Denys; Jiménez Villarreal, J.; Carranza Rosales, María del Pilar; Guzmán Delgado, Nancy Elena; Leyva Orasma, C.; Viveros Valdez, José Ezequiel; Morán Martínez, Javier (2015)
Formaldehyde (FA) is an environmental xenobiotic, which is genotoxic and carcinogenic to humans and animals; it induces DNA damage, mutations, and clastogenicity during critical cytogenetic events. FA-mediated oxidative stress is an important mechanism that has been associated with the induction of cytotoxic and genotoxic damage. Therefore, the objective of this study was to evaluate the dispersion of sperm chromatin and reproductive parameters induced by exposure to different concentrations of FA in Wistar rats. Compared to the percentage of sperm with fragmented DNA in the control group (18.10 ± 8.62%), the percentage of sperm with fragmented DNA increased following exposure to 5, 10, and 30 mg FA/kg body weight (29.60 ± 8.44, 85.20 ± 20.94 and 96.0 ± 7.87, respectively; P = 0.0001). Histopathological alterations were evident, especially in the seminiferous tubules. In conclusion, this study provides experimental evidence concerning the genotoxicity of FA, with particular reference to the decreased sperm concentration and motility and increased dispersion of DNA chromatin in rats.